2021
DOI: 10.3390/ijerph18158205
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Therapy for Children with Special Health Care Needs and Their Parents: A Systematic Review and Meta-Analysis

Abstract: Context: Acceptance and Commitment Therapy (ACT) is an emerging treatment for improving psychological well-being. Objective: To summarize research evaluating the effects of ACT on psychological well-being in children with special health care needs (SHCN) and their parents. Data Sources: An electronic literature search was conducted in PubMed, Web of Science, Ovid/EMBASE and PsycINFO (January 2000–April 2021). Study Selection: Included were studies that assessed ACT in children with SHCN (ages 0–17y) and/or par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…All studies were of moderate to high quality. These studies have investigated the effects of ACT on depression and anxiety in populations of children ( 26 , 29 , 36 , 45 ) or adults, mental health patients ( 23 , 28 , 30 , 38 , 40 , 41 , 44 ), patients with different cancers or multiple sclerosis ( 25 , 31 , 34 , 37 , 42 ), people with audiological problems ( 32 ), parents or caregivers of children with mental or physical illnesses ( 22 , 24 , 26 , 39 ) as well as normal people. Most of the findings of these studies have been reported by comparing ACT effects with waiting list control groups, treatment as usual and CBT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies were of moderate to high quality. These studies have investigated the effects of ACT on depression and anxiety in populations of children ( 26 , 29 , 36 , 45 ) or adults, mental health patients ( 23 , 28 , 30 , 38 , 40 , 41 , 44 ), patients with different cancers or multiple sclerosis ( 25 , 31 , 34 , 37 , 42 ), people with audiological problems ( 32 ), parents or caregivers of children with mental or physical illnesses ( 22 , 24 , 26 , 39 ) as well as normal people. Most of the findings of these studies have been reported by comparing ACT effects with waiting list control groups, treatment as usual and CBT.…”
Section: Resultsmentioning
confidence: 99%
“…), instead of focusing on comparative experiments investigating two different therapeutic approaches. In addition, although most studies found ACT to be effective in improving the symptoms of anxiety and depression in children and adolescents ( 26 , 29 , 36 , 45 ), some studies considered the available evidence to be insufficient for its effectiveness in this population ( 28 , 40 ). Thus, future research with large sample sizes should focus on treating anxiety and depression symptoms in children and adolescents to determine the true effect size of ACT in this important population.…”
Section: Discussionmentioning
confidence: 99%
“…Having a counselor or school psychologist available to periodically monitor these students can help facilitate timely support and treatment. Therapeutic interventions, such as cognitive behavior therapy, acceptance and commitment therapy, and general supportive and reflective listening in the spirit of unconditional positive regard, can be helpful (Levy et al, 2016;Parmar et al, 2021). If these resources are not available in the school setting, faculty may provide the families referrals for further treatment.…”
Section: Social-emotional and Behavioralmentioning
confidence: 99%
“…These studies provide advice on promising new directions and evidence for the effectiveness of psychological interventions that can be used in V/DSD [7][8][9].…”
Section: Paediatric Clinical Psychologymentioning
confidence: 99%
“…Searching paediatric psychology intervention studies in English language peer-reviewed journals reveals intervention studies and reviews of effectiveness reporting outcomes of psychological interventions conducted with larger clinical groups such as children and young people with cancer, diabetes, epilepsy, colorectal disease, or cystic fibrosis. These studies provide advice on promising new directions and evidence for the effectiveness of psychological interventions that can be used in V/DSD [7‒9].…”
Section: Paediatric Clinical Psychologymentioning
confidence: 99%